Gene expression pattern of K transporter GhHAK5 gene of potassium efficient and in-efficient cotton cultivars based on morphological physiognomies as affected by potassium nutrition and reduced irrigation - Muhammad Naeem Akhtar; Tanveer ul Haq; Muhammad Waseem Akhtar; Ghulam Abbass (Journal of Cotton Research, 2023)
Abstract Background Under K deficiency the uptake and distribution pattern in plant cells is mediated through different transport proteins and channels which were controlled by specific gene family. Therefore, a hydroponic experiment was conducted under control condition for testing the gene expression pattern of the K transporter under adequate and low K supply levels. After that, a 2-year field experiment was conducted to evaluate five selected cotton cultivars (four K-efficient cultivars, viz., CIM-554, CYTO-124, FH-142, IUB-2013, and one K non-efficient, BH-212) screened from the initial hydroponics culture experiment and two levels of potassium (0 K2O kg·ha−1 and 50 K2O kg·ha−1) were tested under reduced irrigation (50% available water content; 50 AWC) and normal irrigation conditions (100% available water content; 100 AWC). Result Results revealed that the transcript levels of GhHAK5aD in roots were significantly higher in K+ efficient cultivars than that in K+ non-efficient cultivars. The GhHAK5aD expression upon K+ deficiency was higher in roots but lower in shoots, indicating that GhHAK5aD could have a role in K+ uptake in roots, instead of transport of K+ from root to shoot. Similarly, under field conditions the cultivar FH-142 showed an increase of 22.3%, 4.9%, 2.4%, and 1.4% as compared with BH-212, IUB-2013, CYTO-124, and CIM-554, respectively, in seed cotton yield (SCY) with K application under reduced irrigation conditions. With applied K, the FH-142 showed an increase in net photosynthetic rate by 57.3% as compared with the rest of the cultivars under reduced irrigation over K control. However, the overall performance indicators of K-efficient cultivars like FH-142, CYTO-124, CIM-554, and IUB-2013 were better than BH-212 (K in-efficient) under reduced irrigation conditions with applied K at 50 kg·ha−1. Fiber quality trait improved significantly with K application under water deficit. The increase in micronaire was 3.6%, 4.7%, 7.8%, 3.4%, and 6.7% in BH-212, IUB-2013, CIM-554, CYTO-124, and FH-142, respectively, with K application at 50 kg·ha−1 over without K application under reduced irrigation conditions during the cotton growing season. Similarly, the cultivars FH-142 increased by 12% with K application under reduced irrigation as compared with other cultivars. The performance of K-efficient cultivars under reduced irrigation conditions was 30% better in SCY and quality traits with the application of K at 50 kg·ha−1 as compared with K-non-efficient cultivars. Similarly, water use efficiency (WUE) (40.1%) and potassium use efficiency (KUE) (20.2%) were also noted higher in case of FH-142 as compared with other cultivar with K application under reduced conditions. Conclusion Higher expression of GhHAK5aD gene was observed in K-efficient cultivars as compared with K-non-efficient cultivars in roots indicates that GhHAK5aD may be contributing to genotypic differences for K+ efficiency in cotton. K-efficient cotton cultivars can be used for the low-K environments and can also be recommended for general cultivars.